MAKNA PESAN DALAM DINAMIKA KONFLIK INTERPERSONAL PADA FILM WEB SERIES “TERIMA KOST PUTRI” - Gunawan, Muhammad Khalil (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
Significant changes in the film industry encourage access via the YouTube platform and are no longer limited to the big screen. The current development of YouTube in Indonesia, with the emergence of web series on YouTube channels, has become a popular way to pass the time or relax after activities. Web series films are a form of public viewing that incorporates modern concepts. The researchers researched the web series